Integrasi Kecerdasan AI dalam Pendidikan Islam Modern - Indah Nur Lathifiyah; Miranda Cahyani; Yahya Ashari (Sujud: Jurnal Agama, Sosial dan Budaya, 2026)
The rapid development of digital technology in the modern era has brought significant changes to various aspects of life, including the field of education. One of the fastest-growing technologies is Artificial Intelligence (AI), which is capable of supporting data analysis, decision-making, and enhancing the teaching and learning process in a more effective and efficient manner. This study aims to examine the role of Artificial Intelligence in supporting modern Islamic education and to explore how AI can be integrated into the educational process without compromising Islamic values. The research employs a qualitative approach using a literature review method by analyzing relevant journals, books, and other scholarly sources. The findings indicate that the utilization of AI in Islamic education can improve learning effectiveness through adaptive learning systems, faster assessment processes, and broader access to Islamic knowledge resources. However, the implementation of AI must remain aligned with fundamental Islamic educational values, such as Tawhid (the Oneness of God), Amanah (trustworthiness), and responsibility, ensuring that technology does not replace the educator's role as a moral and spiritual guide. With an appropriate approach, the integration of AI can serve as a strategic tool to enhance the quality of Islamic education while preserving the spiritual values that form its essential foundation.